Isocitrate Lyase and Succinate Semialdehyde Dehydrogenase Mediate the Synthesis of α-Ketoglutarate in Pseudomonas fluorescens - Alhasawi, Azhar A.; Thomas, Sean C.; Tharmalingam, Sujeethar; Legendre, Felix; Appanna, Vasu D. (Frontiers in Microbiology, 2019)
Glycerol is an important by-product of the biodiesel industry and its transformation into value-added products is being actively pursued in order to improve the efficacy of this renewable energy sector. Here we report that the enhanced production of α-ketoglutarate (KG) effected by Pseudomonas fluorescens in a mineral medium supplemented with manganese (Mn) is propelled by the increased activities of succinate semialdehyde dehydrogenase (SSADH), γ-aminobutyric acid aminotransaminase (GABAT), and isocitrate lyase (ICL). The latter generates glyoxylate and succinate two key metabolites involved in this process. Fumarate reductase (FRD) also aids in augmenting the pool of succinate, a precursor of succinate semialdehyde (SSA). The latter is then carboxylated to KG with the assistance of α ketoglutarate decarboxylase (KDC). These enzymes work in tandem to ensure copious secretion of the keto-acid. When incubated with glycerol in the presence of bicarbonate (HCO3-), cell-free extracts readily produce KG with a metabolite fingerprint attributed to glutamate, γ-aminobutyric acid (GABA), succinate and succinate semialdehyde. Further targeted metabolomic and functional proteomic studies with HPLC, NMR and gel electrophoresis techniques provided molecular insights into this KG-generating machinery. RT-qPCR analyses revealed the transcripts responsible for ICL and SSADH were elevated in the Mn-supplemented cultures. This is the first report of a metabolic network where ICL and SSADH orchestrate the enhanced production of KG from glycerol. It affords a biochemical process that can be harnessed to improve the efficiency of the biodiesel industry.